2021
DOI: 10.21608/bmfj.2021.17419.1078
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Corticosteroid Therapy: A Comparative Study of Dexamethasone and Betamethasone Effects on Fetal Doppler Indices

Abstract: Background: Preterm delivery, defined as delivery before 37 weeks of pregnancy, is the leading global reason for neonatal mortality and morbidity. Preterm neonates have serious

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
0
0
Order By: Relevance
“…groups, but the increase was higher in Dexamethasone compared to Betamethasone, although this significant increase was in normal range according to gestational age, The most significance difference in both groups was between Pretreatment & Post-treatment 1 week. These finding are in agreement with Elmorsy et al, [7] that reported there was significant increase in umbilical artery RI in both groups (P < 0.001). These Results were on disagreement with, the study of Ahmed et al, [8] as reported that in terms of Doppler Indices, the umbilical artery pulsatility index (PI) and resistive index showed a statistically significant reduction after Dexamethasone administration (p <0.001).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…groups, but the increase was higher in Dexamethasone compared to Betamethasone, although this significant increase was in normal range according to gestational age, The most significance difference in both groups was between Pretreatment & Post-treatment 1 week. These finding are in agreement with Elmorsy et al, [7] that reported there was significant increase in umbilical artery RI in both groups (P < 0.001). These Results were on disagreement with, the study of Ahmed et al, [8] as reported that in terms of Doppler Indices, the umbilical artery pulsatility index (PI) and resistive index showed a statistically significant reduction after Dexamethasone administration (p <0.001).…”
Section: Resultssupporting
confidence: 93%
“…We reported that there was significance decrease in MCA RI in Dexamethasone group between Pretreatment & Post-treatment 1 weeks but still in normal range, our results supported by Elsnosy et al, [9] which demonstrated that maternal dexamethasone administration to pregnant women at risk of preterm labor improves the blood flow of the maternal uterine artery, fetal MCA, descending aorta and umbilical artery 24 h after its administration. Similarly, Elmorsy et al [7], reported a significant decrease in Middle cerebral artery RI in dexamethasone group (P<0.001). Also ,Wahby et al, [10] they recruited 50 women who received dexamethasone with follow up of Doppler values (UA and MCA) after 60 hours from the first dose of dexamethasone and revealed no significant changes regarding UA Doppler studies with mean RI difference was 0.013 and mean PI was ~0.97 (1%).…”
Section: Resultsmentioning
confidence: 72%